Comment on 'Targeted Ciphers for Format‐Preserving Encryption' from Selected Areas in Cryptography 2018. (2nd May 2021) - Wang, Dachao; Wang, Baocang; Ping, Yuan
Abstract: Format‐preserving encryption (FPE) allows encrypting plaintexts while preserving a specific format. In Selected Areas in Cryptography 2018, two targeted ciphers were proposed as new FPE schemes. The second scheme was designed with an algorithm called Mix–Swap–Unmix that is shown to be equivalent to a particular matching exchange process under a specific setting. In this comment paper, we prove that the matching exchange process is invalid. As a result, this equivalence does not exist.